2004
DOI: 10.1074/jbc.m312801200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Autoregulation of the Promoter for the Latency-associated Nuclear Antigen of Kaposi's Sarcoma-associated Herpesvirus

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) or human herpesvirus 8 has been established as the etiological agent of Kaposi's sarcoma and certain AIDS-associated lymphomas. KSHV establishes latent infection in these tumors, invariably expressing high levels of the viral latency-associated nuclear antigen (LANA) protein. LANA is necessary and sufficient to maintain the KSHV episome. It also modulates viral and cellular transcription and has been implicated directly in oncogenesis because of its ability to bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 86 publications
(84 reference statements)
1
74
2
Order By: Relevance
“…Both N-terminal LANA (N-LANA) and C-terminal LANA (C-LANA) are essential for function. N-LANA associates with mitotic chromosomes via binding histones H2A/H2B, and C-LANA simultaneously binds KSHV terminal repeat (TR) DNA (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Thus, LANA tethers the viral genome to host chromosomes and distributes viral DNA to daughter nuclei during mitosis.…”
Section: Oss-mentioning
confidence: 99%
“…Both N-terminal LANA (N-LANA) and C-terminal LANA (C-LANA) are essential for function. N-LANA associates with mitotic chromosomes via binding histones H2A/H2B, and C-LANA simultaneously binds KSHV terminal repeat (TR) DNA (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Thus, LANA tethers the viral genome to host chromosomes and distributes viral DNA to daughter nuclei during mitosis.…”
Section: Oss-mentioning
confidence: 99%
“…Transcription initiation has been mapped to a single major start site that functions largely through a strong core initiator element, with no apparent enhancer or upstream promoter regulatory factors (11,12). The initiation site of the latency transcript lies within the 5= untranslated region (UTR) of the complementary strand transcript for K14/ORF74 (viral G protein-coupled receptor [vGPCR]), which is expressed primarily in lytically induced B cells but is also detected in most KSHV-infected tissues and has been implicated in the pathogenesis of KS (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…The latency transcripts have complex structures, with multicistronic messages and several alternative promoters, as well as lytic gene promoters for both sense and antisense orientations. Proper regulation of these various transcripts is essential for viral persistence and host cell survival.Transcriptional regulation and mRNA processing of the KSHV major latency transcripts have been investigated in some detail (8,9,(11)(12)(13)(14)(15)(16). Transcription initiation has been mapped to a single major start site that functions largely through a strong core initiator element, with no apparent enhancer or upstream promoter regulatory factors (11,12).…”
mentioning
confidence: 99%
“…In KSHV-infected tumors, LANA is a predominant latent protein and exhibits multiple functions related to viral genome replication, transcription regulation, and cell proliferation (10,14,32). It has been shown that LANA autoactivates its own promoter; thus, the expression of LANA is maintained consistently at a high level by the regulation of this positive-feedback loop (33). High expression of LANA in KSHV-infected cells is one strategy for the virus to establish and maintain latent infection because down regulation of LANA expression results in disruption of viral latency (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%